Ranking pharmaceutical companies on clinical trial diversity. (10th February 2023) - Varma, Tanvee; Miller, Jennifer E
Abstract : Measuring the diversity of clinical trial participants can spur companies to do better, argue Tanvee Varma and Jennifer E Miller